The elegance of the hedgehog [compact disc, unabridged] - Barbery, Muriel, 1969- (Highbridge Co., 2009)
The lives of 54-year-old concierge Reneé Michel and extremely bright, suicidal 12-year-old Paloma Josse are transformed by the arrival of a new tenant, Kakuro Ozu.